Three-dimensional evaluation of dental and skeletal effects after treatment with Alt-RAMEC and facemask protocol on the treatment of Class III malocclusion - Sitaropoulou, Vasiliki (My University, 2015)
Sınıf III Malokluzyonların tedavisinde Alt-RAMEC ve yüz maskesi protokolünün dental ve iskeletsel etkilerinin üç boyutlu değerlendirilmesi Amaç: Bu retrospektif çalışmanın amacı, büyüyen hastalarda Alt-RAMEC ve yüz maskesi protokolü ile tedavi sonrası iskeletsel, dental ve yumuşak dokularda meydana gelen etkileri araştırmak ve sonuçları aynı yaşta, aynı iskeletsel probleme sahip tedavi edilmemiş hasta grubu ile karşılaştırmaktır. Gereç ve Yöntem: Bütün kayıtlar Marmara Üniversitesi Ortodonti stanbul, Türkiye) arşivinden alınmıştır. Çalışma grubu, maksiller retrognatiye sahip 20 tane Sınıf III hastadan oluşturulmuştur (ortalama yaş: 9,74±1,46 yıl). Genişletme ve daraltma protokolü 9 hafta devam etmiştir. Daha sonra hastalar yüz maskesi ile tedavi edilmiş (ortalama süre 7 ay) ve retansiyon için 4 ay boyunca Sınıf III Bionator kullandırılmıştır. Tedavi öncesi (T0), genişletme sonrası (T1) ve retansiyon sonrası (T2) alınan konik ışınlı bilgisayarlı tomografi (CBCT) ve üç boyutlu (3D) fotoğraflar değerlendirilmiştir. Bu çalışma grubu 16 kişiden oluşan, kayıtları bir çift sefalometrik röntgen ve 3D fotoğrafları kapsayan kontrol grubu ile karşılaştırılmıştır. Bulgular: A noktasının belirgin bir şekilde ileri (3,49 mm) ve aşağı (1,15 mm) doğru hareketi sağlanmıştır. Üst keser diş eğimleri azalırken, alt keser diş eğimlerinde anlamlı bir değişiklik gözlenmemiştir. Üst interkanin ve intermolar mesafeler belirgin bir şekilde artmıştır. Nazal ve zigomatik kemikler belirgin bir şekilde öne hareket etmiş, internazal ve interzigomatik mesafeler belirgin bir şekilde artmıştır. B’ noktası ve Pog’ hariç olmak üzere tüm yumuşak doku noktaları ileri hareket etmiştir. Sonuçlar: Çalışmada anlatılan tedavi protokolü iskeletsel Sınıf III malokluzyonun düzeltilmesinde oldukça etkili bir yöntemdir. Alt-RAMEC, Sınıf III Malokluzyon, Yüz Maskesi, Maksiller Protraksiyon, Hızlı Maksiller Genişletme

Three-dimensional evaluation of dental and skeletal effects after treatment with Alt-RAMEC and facemask protocol on the treatment of Class III malocclusion Aim: The aim of this retrospective study was to investigate the effects on skeletal, dental and soft tissue structures in growing patients after the treatment with facemask following The Alternate Maxillary Expansions and Constrictions (Alt-RAMEC) protocol and to compare the results with an untreated group of patients of the same age and skeletal problem. Materials and Methods: All the records were selected from the archive of the Orthodontic Department of Marmara University, Istanbul, Turkey. The study group consisted of 20 Class III maxillary retrognathia patients (mean age: 9.74±1.46 years). The expansion and constriction protocol lasted for 9 weeks. Additionally, the patients were treated with facemask (mean duration 7 months) and a Class III bionator for retention, for 4 months. The Cone Beam Computed Tomography (CBCT) images and three dimensional (3D) photos taken before (T0) and after expansion (T1) and after retention (T2) were evaluated. This study group was compared with a control group of 16 patients whose records included a pair of cephalometric x-rays and 3D photos. Results: A significant forward (3.49 mm) and downward (1.15 mm) displacement of A point was achieved. Upper incisors’ inclinations decreased, while lower incisors’ inclinations did not change significantly. Upper intercanine and intermolar distances increased significantly. Nasal and zygomatic bones moved significantly forward and internasal and interzygomatic distances increased significantly. All the soft tissue points moved forward, apart from B’ and Pog’ which did not show a significant change. Cocnlusions: The treatment protocol described in this study was very affective for correcting Class III malocclusion. Key Words: Alt-RAMEC, Class III Malocclusion, Facemask, Maxillary Protraction, Rapid Maxillary Expansion.
Keywords: Ortodonti